2014
DOI: 10.1097/opx.0000000000000365
|View full text |Cite
|
Sign up to set email alerts
|

Depth-of-Field of the Accommodating Eye

Abstract: PurposeTo obtain experimental values of the depth-of-field (DOFi) of the human eye for different accommodative states.MethodsFirst, the monochromatic ocular wavefront of seven eyes from young subjects (mean [±SD] age, 29.7 [±7.7] years) was measured at eight different accommodative demands (ADs) (from −1 to 6 diopters [D] in steps of 1 D). Then, in a second part, accommodation was paralyzed and an adaptive optics system was used to correct the aberrations of the paralyzed eye and to simulate, with the aid of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…2 ). The accommodation measures exhibited the expected properties, a small lag at “near” and a small lead at “far” (Bernal-Molina et al 2014 ; Seidemann and Schaeffel 2003 ). At “near”, participants loaded their accommodative system with an average of 26% out of age predicted maximum level (min–max 20–46%).…”
Section: Resultsmentioning
confidence: 87%
“…2 ). The accommodation measures exhibited the expected properties, a small lag at “near” and a small lead at “far” (Bernal-Molina et al 2014 ; Seidemann and Schaeffel 2003 ). At “near”, participants loaded their accommodative system with an average of 26% out of age predicted maximum level (min–max 20–46%).…”
Section: Resultsmentioning
confidence: 87%
“…It has been demonstrated that the eye uses its depth of field both in far and near vision in order to increase the subjective AA. 33 In addition to the limitation imposed by photoreceptor sampling and photonic noise, depth of field occurs because of the presence of HOAs when the pupil is larger during relaxed accommodation, 24 and as a consequence of the accommodative miosis. 34…”
Section: The Influence Of Aberrations On the Subjective And Objectivementioning
confidence: 99%
“…and Tucker & Charman noticed, this dependence is greatly affected by its interaction with letter size. It also depends on other parameters such as luminosity, contrast, and state of accommodation of the eye . Although various studies have been carried out to understand the effects of high order, monochromatic aberrations on DOFi, the effects of another important aberration – the longitudinal chromatic aberration (LCA) on accommodation error have not been explored in depth so far.…”
Section: Introductionmentioning
confidence: 99%